Amorphous NiB/carbon nanohybrids: synthesis and catalytic enhancement induced by electron transfer. Issue 97 (4th October 2016) - Liu, Weikai; Chen, Ruifen; Liu, Lijun; Li, Shuangzhi; Xue, Zhiyong; He, Chiyang
Abstract : Amorphous NiB/C shows synergistic catalysis for 4-nitrophenol reduction, induced by the electron transfer from NiB alloy to carbon support. Abstract : Catalytic conversion of hazardous 4-nitrophenol (4-NP) to 4-aminophenol over cost-effective catalysts is environmentally and commercially desired. Herein, we have synthesized amorphous NiB/C nanohybrids through a solution-phase reduction using pre-oxidized carbon nanoparticles as support. The amorphous catalyst shows promising activity towards the reduction of 4-NP with a high k n (3.640 s −1 mg −1 ) and low activation energy (35.4 kJ −1 mol −1 ). The catalytic activity highly depends on the carbon support and the crystalline degree of NiB alloy. An electron-transfer-induced catalytic mechanism is proposed to explain the catalytic performance of NiB/C. It is found that the electron transfer in metal/support interfaces makes NiB alloy electrophilic, favoring the adsorption of reactants, generation of active hydrogen and hydrogenation of 4-NP. The amorphous NiB/C catalyst can be recycled five times without obvious loss of activity. Our work demonstrates an example to explore the catalytic behavior of amorphous NiB/C catalyst, which may shed light on developing other advanced amorphous catalysts for 4-NP reduction.